(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the theoretical and practical aspects of the methodology for integrating foreign andragogic approaches into the vocational education system. Andragogy is considered a scientific approach that takes into account the educational needs, motivation and experience of adult education. The organizational and pedagogical conditions, integration mechanisms and implementation stages of adapting foreign andragogic approaches to the national vocational education system are substantiated. The results of the study serve to improve the quality of vocational education, develop the professional competencies of adults, and adapt the educational process to the requirements of the modern labor market.